498 PERSISTENT FIFTH AORTIC ARCH IN A PATIENT WITH CHARGE SYNDROME: A CASE REPORT AND SYSTEMATIC REVIEW OF LITERATURE. (15th December 2022) - Ferraioli, Mario; Nocilla, Alessandra; Vincenza Polito, Maria; Malinconico, Marisa; Coppola, Guido; Ferrara, Francesco; Ciccarelli, Michele; Vecchione, Carmine; Galasso, Gennaro
Abstract: Background: CHARGE syndrome (CS) is a rare genetic disease characterized by a constellation of clinical findings including Coloboma, Heart defects, choanal Atresia, Retardation of growth and/or development, Genitourinary malformation and Ear abnormalities. We present a case of persistent fifth aortic arch (PFAA), an extremely rare congenital anomaly of aortic arch (AA), in a child with genetically confirmed CS and perform a systematic review of published studied, in an effort to examinate the distribution of congenital heart diseases (CHDs) and their impact in CHARGE patients. Case presentations and results: A 12 years-old child was referred to our echocardiography laboratory for atypical chest pain. He had bilateral ocular coloboma, left hypoacusis, scoliosis, mild motor impairments, nocturnal enuresis, micropenis and facial dysmorphisms. Molecular diagnostic testing identified a de novo mutation (variant c.5290_5300+10del) in the CHD7 gene and CS was diagnosed. Echocardiography showed a single posterolateral papillary muscle and a cleft of anterior mitral leaflet. Interestingly, AA had a double-lumen appearance without Doppler signs of coarctation. A PFFA was hypothesized and then confirmed at angioCT. A systematic review of the literature was performed according to PRISMA guidelines. All published articles reporting the association CS and CHDs were chosen. A total of 975 records were identified. After the screening of title and abstract, assessed for eligibility were 219 papers. Finally, inclusion and full-text analysis was made in 60 studies, of which 37 case reports and 23 case series. We found that ventricular septal defects emerged as the most prevalent heart defect (32%), followed by atrial septal defects reported in 23% of cases. Complex CHDs were also described. Interestingly, AA abnormalities were reported in a high percentage (27%) of patients, right AA in 20% in association or not with aberrant subclavian artery and vascular ring, interrupted AA in 5% of cases, as well as aortic coarctation in 10%. Of note, almost half of the cases (49%) required cardiac surgery, mostly performed within 1 year from birth and, although outcome was available in a minority of patients, the death was reported in almost 30%. Conclusions: Our case is the first that reports PFFA in CS and may be mistaken for AA dissection. In comparison with other syndromic diseases, a high prevalence of AA abnormalities was found in patients with mutations in the CHD7 gene.